Chemical composition of the essential oil of bitter fennel (Foeniculum vulgare subsp. piperitum) - Akgul, M Ozcan, A (Journal of Spices and Aromatic Crops, 2001)
The composition of the essential oil obtained by steam distillation from seeds of bitter fennel (Foeniculum vulgare subsp. piperitum) was analysed by GC/MS. The presence of atleast seventeen compounds was demonstrated. They correspond to 99.95% of the oil. Methyl chavicol was the main constituent of the oil (47.09%), followed by limonene (29.07%), fenchone 03.43%), a-terpinene (2.5%), fenchyl acetate (exo) 0.95%) and cis-b-ocimene (1.41%). Trans-anethole was not detected. Therefore, it is concluded that the oil of Turkish bitter fennel is rich in methyl chavicol.